A study on flight muscle system in coleoptera and fuel cell catalyst toward self-powered biological flapping machine - Vo Doan, Tat Thang (2016)
Miniature wireless device that has the capability of extracellular recording and electrical stimulation enables us to validate the hypothesis of insect maneuver in free flight. Such behavior might be different from what we had experienced for long time in tethered condition. In addition, it would allow solving the difficulty of defining the role of the small muscles in flight. In this report, the function of 3rd axillary sclerite (3Ax) muscle and subalar muscle in coleopteran will be evaluated to achieve the graded turn and braking control in free-flying insect. The coleopteran 3Ax muscle, which is thought to have the function of folding the wing, in fact, plays a key function in steering during flight. The electrical stimulation of 3Ax muscle in free-flying insect is able to induce the graded ipsilateral turns that was also confirmed in tethered condition. Along with 3Ax muscle, the subalar muscle is an important muscle that pulls the posterior part of the wing base to regulate the wing rotation during flight. The electrical stimulation of the muscle caused the increment of wing rotation angle and thus leaded to the increase in drag in free flight. A biological flapping machine can be developed by controlling these muscles in the living insect. Toward self-powering feature, fuel cell can be used as a secondary power source to charge the battery of the electronic board mounted on the living insect. The fuel cell performance can be improved by using electrocatalyst to increase the activity of the cathode. The B-doped Pd (Pd-B) nanoparticle catalyst was synthesized for the cathode by the remarkably facile stepwise electroless deposition method. The Pd-B nanoparticles exhibit superior catalytic activity to the synthesized pure Pd and the commercial Pd/C.